Cooperation in Greater Mekong Sub-region (GMS): Implication and Lesson Learned for Indonesia’s Industrial Development - La Ode Nazaruddin (Policy & Governance Review, 2022)
The progress of Greater Mekong Sub-region (GMS) is presumed to pose challenges and implications for Indonesia. This study has the aim to investigate the impact of the recent development of sub-regional cooperation and cross-border economic development within GMS on Indonesia’s industrial development. Using qualitative methods, this study analyzed some variables, i.e., the background of GMS cooperation, infrastructure and investment progress, and Indonesia’s related economic policies and development. Data and information were collected from many sources (i.e., statistical databases, articles, newspapers, websites, un- and published documents, etc.) and presented qualitatively. This study found that GMS economic cooperation and development have lessons learned and implications for the industrial development in Indonesia. The efficiency of the service sector within GMS was contributed by the successful implementation of policies on infrastructure development since the beginning of the 1990s. The flying geese behavior and industrial fragmentation within GMS were contributed by a different stage of industrial development, different comparative advantage, and improvement of the service sector. The implication of GMS cooperation for Indonesia is the importance of public policy stability, more attractive investment of high-end products in GMS than Indonesia, and potential diminishing of Indonesia’s export.